PENERAPAN SISTEM PEMANTAUAN KUALITAS AIR BERBASIS INTERNET OF THINGS UNTUK MENINGKATKAN PRODUKTIVITAS BUDIDAYA IKAN GURAMI DI DUSUN BAKALAN - Sujito Sujito (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Several carp farming farmers in Bakalan Hamlet expressed worry about frequent disease outbreaks, sluggish development, and carp mortality due to water quality that dropped below the culture requirement. In response to these issues, the water quality monitoring system was developed. The information gathered by the sensors will be transmitted to the Thingspeak webserver. Accessing the monitoring system and determining the current state of water quality measures can be accomplished by using a smartphone. Assume that the measurements for water quality do not fulfill the standards for cultured water in this case. Suppose the water quality parameters do not match the cultured water quality standards. In that case, the information will be displayed on a web interface via a smartphone so that gurami farmers know what steps will be taken to overcome this. This water quality monitoring system can benefit carp farmers so that the production of carp aquaculture is maximized. The result of this community service activity was that the tool was successfully made and worked well. The existence of this tool greatly helped the partner's response to this activity.